Screening for nitrite producing Bacillus licheniformis from various origins : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology, Massey University, New Zealand - Mistry, Jalak (Massey University, 2024)
Nitrite, which has been considered a chemical danger, can cause infant methemoglobinemia. Bacillus licheniformis is one of the spores forming nitrite-producing bacteria that serves as a potential risk in the dairy industry based on its roles in foodborne illness and dairy spoilage. This study was carried out to assess the nitrite production by 10 strains of B. licheniformis under different environmental conditions. B. licheniformis isolated in this research comes from various sources, including a pasteurisation system, tuber feed, and milk samples obtained from the Massey University Microbiology Lab. This research focused on five different temperatures (25°C, 30°C, 37°C, 55°C and 60°C) approximate processing conditions found in the dairy industry checking the B. licheniformis growth and measuring optical density at 570nm at all five temperatures. This study also examined the production of nitrite in aerobic and anaerobic conditions. All isolated strains were able to convert nitrate into nitrite at all 5 temperatures at both aerobic and anaerobic conditions except some isolates from spring (15, 17) and winter (36, 43, 50,55) convert nitrite into some other nitrogenous compounds under 60°C anaerobic conditions, suggesting that there is a potential variability in metabolic pathways. However, oxygen availability does not affect nitrate reduction. It was observed that optimal growth occurred between 30°C and 55°C. These findings have shown the likely health hazards associated with B. licheniformis, as the organism can convert nitrate into nitrite. The finding suggests a need for further research on the metabolic pathways of these isolates to understand their behaviour and mitigate associated risks.
Keywords: 300607 Food technology